PENCEGAHAN SEXUAL VIOLENCE PADA ANAK MELALUI UNDERWEAR RULE CAMPAIGN - Suharto, Idola Perdana Sulistyoning; Yunalia, Endang Mei; Haryuni, Sri; Etika, Arif Nurma; Rahayu, Kun Ika Nur; Geragam, Lisna Watie; Tatan, Yohanes (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Sexual violence is any sexual activity (acts, comments, human trafficking for sexual purposes) against another person using coercion, carried out by anyone regardless of their relationship with the victim, and under any circumstances. Cases about sexual violence against children are overgrowing. The causes of sexual violence against children consist of several factors: family environmental factors, economics, relationships, technology and mass media, psychology, and lack of religious knowledge. Sexual violence against children has any impact not only physical but also psychological aspects of children. Prevention efforts can be made by providing sexual education to children. One method of sexual education in children is the Underwear Rule Campaign. This activity carried out in the form of counseling. Before counseling, respondents will be given a pre-test, and after counseling, respondents will be given a post-test. The result of pre-test and post-test scores were tested by paired t-test. This activity results in a significant difference in the average pre-test and post-test scores, with the post-test mean scores being higher than the pre-test scores. — Sexual violence (Kekerasan seksual) didefinisikan sebagai setiap kegiatan seksual (tindakan, komentar, perdagangan manusia untuk tujuan seksual) terhadap orang lain dengan adanya paksaan, yang dilakukan oleh orang tidak memandang hubungannya dengan para korban, dan dalam situasi apapun. Kasus kekerasan seksual pada anak berkembang sangat pesat. Penyebab terjadinya kekerasan seksual pada anak terdiri dari beberapa factor, yaitu factor lingkungan keluarga, ekonomi, pergaulan, teknologi dan media massa, psikologi, dan kurangnya pendalaman agama. Kekerasan seksual pada anak memiliki dampak pada aspek fisik dan psikologi anak. Upaya pencegahannya bisa dilakukan dengan memberikan pendidikan seksual pada anak. Salah satu metode pendidikan seksual pada anak adalah dengan menggunakan Underwear Rule Campaign. Kegiatan ini dilakukan dalam bentuk penyuluhan. Sebeleum dilakukan penyuluhan, responden akan diberi soal untuk pre-test, setelah penyuluhan, responden diberikan soal untuk post-test. Rerata nilai pre-test dan post-test diuji dengan uji statistik T berpasangan. Hasil dari kegiatan ini adalah ada perbedaan signifikan rerata nilai pre-test dan post-test dengan rerata nilai post-test lebih tinggi bila dibandingkan nilai pre-test.